Establishment of Islamic Banking System in Afghanistan: Factors Have Led to the Late Establishment of Islamic Banking - Salim, Mohammad Salim (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2020)
This article aims to find the factors causing the underdevelopment of Islamic banking in Afghanistan. The method used is qualitative with a sociology of religion approach and is included in the category of policy research. The results of this study indicate that almost all of Afghanistan's population is Muslim and 90% of Afghans refuse the establishment of conventional banks on the grounds of interest. As for the causes of the delay in Islamic banking in Afghanistan, namely: First, political instability. Second, the economy is weak. Third, lack of legislative support. Fourth, support from scholars. Fifth, lack of public information. Sixth, the lack of experts in their fields.